Cellulose from lignocellulose kitchen waste and its application for energy and environment: bioethanol production and dye removal. Issue 2 (15th March 2021) - Ganguly, Preetha; Khan, Ashis; Das, Papita; Bhowal, Avijit
ABSTRACT: Every year about millions of tons of raw feedstocks having a potential value in solid waste is confined into landfills. One of the present challenges for ecological engineering is to develop economically practical and cost-effective technologies to treat waste into value-added by-products. One of the common types of renewable fuel is Bioethanol. The aim of this research was the utilisation of kitchen wastes (onion peels and tea waste) for bioethanol production and wastewater treatment. Hydrothermal (alkali) followed by acidic pre-treatment was reported best technique for both the feedstocks. Pre-treated wastes were further, hydrolysed by Aspergillus sp. for reducing sugar production. The maximum reducing sugar yield reported was 9.50 mg/ml from the onion peels and 4.88 mg/ml from tea waste. The anaerobic condition was maintained for the fermentation process by utilising Saccharomyces cerevisiae. Bioethanol production was maximum from onion peels 0.95, and 0.66 g/g was achieved by utilising tea waste. The other environmental concern today is to evolve an effectual treatment methodology for the reuse of the lignocellulosic substrate. In this context, biomass waste was treated and transform to value-added products such as cellulose and lignin, utilised for crystal violet dye removal. The maximum amount of dye removed was 96% using cellulose. GRAPHICAL ABSTRACT: UF0001